(untitled) (Scottish Historical and Archaeological Internet Reports, 2009)
The origins of the rockshelters at Sand and An Corran are intimately related to past changes in relative sea-level that took place at the close of the last (Late Devensian) glaciation in Scotland. The relative sea-level changes that took place across the North West Highlands at this time resulted from the complex interplay of glacio-isostatic rebound consequent upon regional ice melting (deglaciation) and the influence of glacio-eustatic changes in global ocean volume linked to the melting of ice sheets worldwide. This account describes the interaction of these two key processes and described how the raised shoreline features of Applecross, Raasay and eastern Skye were mostly formed when sea-level was lower (and not higher) than present.